Alois Alzheimer and Gaetano Perusini: Should Man Divide What Fate United? - G. Macchi; C. Brahe; M. Pomponi (Behavioural Neurology)
Three points of interest lie in considering how Alzheimer, and more significantly Perusini, struggled to throw light on the cause of this devastating disease. There is a stimulating possibility that Perusini believed presenile forms of Alzheimer’s disease described the same disease as senile forms. If so this would anticipate current opinion, and reveal Perusini to dissent from Kraepelin. In addition, Perusini may have understood the pathological relationship between neuritic plaques and vascular changes, once more foreseeing the modern view of Alzheimer’s disease. Finally, Perusini and Alzheimer disagreed with Jung's view concerning the relationship between neuropathology and clinical psychiatry. This point highlights the major change occurring at that time from classical neurology to the psychoanalytic era. In his last work (1911) Alzheimer quoted his Italian disciple many times, even speaking of ‘Perusini's cases’ (Perusinischen Fälle). This article is an attempt to change the eponym of Alzheimer’s disease into the Alzheimer-Perusini disease. This is a brief history of a master and his disciple, whose scientific lives were, by events, divided.